Hatching Rate and Survival Rate of Bonylip barb (Osteochilus vittatus; Valenciennes, 1842) on Maintenance Media with Different Water pH - Setiawati, Sulis; Latuconsina, Husain; Dwi Prasetyo, Hamdani (Agrikan Jurnal Agribisnis Perikanan, 2022)
The use of vegetable biopesticides in plantations has long been known, but its application in forestry plant nurseries is generally still not widely practiced by the community. One of the environmental problems has become a global issue, namely the excessive use of pesticides and fertilizers. The use of pesticides that are not in the right dose, inappropriate use, inappropriate benefits and not according to the rules of use can be a source of compounds and pollution containing heavy metals which are very difficult to degrade. Cinnamon biopesticide research was carried out in several locations based on research activities. The collection of cinnamon samples was carried out in the Research Field of the Faculty of Agriculture and the manufacture of biopesticide solutions was carried out at the Forestry Laboratory, Faculty of Agriculture, Khairun University. To test the effectiveness of the biopesticide solution, it was carried out in the Ake Malamo Watershed Management Center and Protected Forest on mangrove/mangrove seedlings. The application of biopesticides is carried out by spraying all parts of the seeds with the appropriate concentration of treatment. Applications were carried out five times with an interval of once every 1 week. Observations were made every week, one day after the application of spraying. The use of fragrant cinnamon biopesticide which was sprayed on mangrove seedlings 5 times 7 days after planting with a concentration of 75% each time was proven to suppress pest attacks so as to increase their growth. This result is better than the control/other treatments.